Application Of Individual Therapy In Patients With Hearing Hallucinations - Zikiriyani, Imas; Lestari, Indri (Yayasan Rumah Ilmu Professor, 2023)
Hallucinations are a symptom of mental disorders where the patient experiences changes in sensory perception, false sensations in the form of sound, sight, taste, touch or smell, the client perceives stimuli that do not actually exist. Objective: to study the application of individual speech therapy in patients with auditory hallucinations. Method: The descriptive case study design method is used in qualitative research. Results: Shows that with individual speech therapy, the patient can direct the patient's attention so that he can control the hallucinations he experiences. Conclusion: Individual speech therapy for patients with auditory hallucinations is effective in controlling hallucinations. Recommendations should consider creating new policies for nurses, particularly ward nurses, to implement consistently, with the aim of reducing the number of patients with mental health problems.